New Carbon Based Materials for Electrochemical Energy Storage Systems: Batteries, Supercapacitors and Fuel Cells - Barsukov, Igor V.; Johnson, Christopher S.; Doninger, Joseph E.; Barsukov, Vyacheslav Z.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
Carbonaceous materials play a fundamental role in electrochemical energy storage systems. Carbon in the structural form of graphite is widely used as the active material in lithium-ion batteries; it is abundant, and environmentally friendly. Carbon is also used to conduct and distribute charge effectively throughout composite electrodes of supercapacitors, batteries and fuel cells. The electronic conductive pathways are critical to delivering and extracting current out of the device. However, many challenges and the understanding of the role of carbon and its stability and efficiency in charge storage applications still exists. This NATO-ARW volume contains a diverse collection of papers addressing the role of carbon in some key electrochemical systems, both conventional and emerging. These papers discuss the latest issues associated with development, synthesis, characterization and use of new advanced carbonaceous materials for electrochemical energy storage. Such systems include: metal-air primary and rechargeable batteries, fuel cells, supercapacitors, cathodes and anodes of lithium-ion and lithium polymer rechargeable batteries, as well as nanocarbon materials of the future.
NEW CARBON MATERIALS FOR SUPERCAPACITORS -- NOVEL CARBONACEOUS MATERIALS FOR APPLICATION IN THE ELECTROCHEMICAL SUPERCAPACITORS -- EFFECT OF CARBONACEOUS MATERIALS ON PERFORMANCE OF CARBON-CARBON AND CARBON-Ni OXIDE TYPES OF ELECTROCHEMICAL CAPACITORS WITH ALKALINE ELECTROLYTE -- HYBRID SUPERCAPACITORS BASED ON ?-MnO2/CARBON NANOTUBES COMPOSITES -- DEVELOPMENT OF SUPERCAPACITORS BASED ON CONDUCTING POLYMERS -- SUPERCAPACITORS: OLD PROBLEMS AND NEW TRENDS -- MODELING POROSITY DEVELOPMENT DURING KOH ACTIVATION OF COAL AND PITCH-DERIVED CARBONS FOR ELECTROCHEMICAL CAPACITORS -- GENERAL PROPERTIES OF IONIC LIQUIDS AS ELECTROLYTES FOR CARBON-BASED DOUBLE LAYER CAPACITORS -- CARBON MATERIALS FOR GAS DIFFUSION ELECTRODES, METAL AIR CELLS AND BATTERIES -- NEW CONCEPT FOR THE METAL-AIR BATTERIES USING COMPOSITES: CONDUCTING POLYMERS / EXPANDED GRAPHITE AS CATALYSTS -- MECHANICALLY RECHARGEABLE MAGNESIUM-AIR CELLS WITH NaCl-ELECTROLYTE -- APPLICATION OF CARBON-BASED MATERIALS IN METAL-AIR BATTERIES: RESEARCH, DEVELOPMENT, COMMERSIALIZATION -- METAL – AIR BATTERIES WITH CARBONACEOUS AIR ELECTRODES AND NONMETALLIC CATALYSTS -- CARBON ANODES FOR LITHIUM-ION BATTERIES -- CARBONACEOUS MATERIALS FOR BATTERIES -- ANODE-ELECTROLYTE REACTIONS IN Li BATTERIES: THE DIFFERENCES BETWEEN GRAPHITIC AND METALLIC ANODES -- PERFORMANCE OF NOVEL TYPES OF CARBONACEOUS MATERIALS IN THE ANODES OF CLAiO’S LITHIUM-ION BATTERY SYSTEMS -- WHY GRAPHITE ELECTRODES FAIL IN PC SOLUTIONS: AN INSIGHT FROM MORPHOLOGICAL STUDIES -- NEW DEVELOPMENTS IN THE ADVANCED GRAPHITE FOR LITHIUM-ION BATTERIES -- MECHANISMS OF REVERSIBLE AND IRREVERSIBLE INSERTION IN NANOSTRUCTURED CARBONS USED FOR Li-ION BATTERIES -- SOME THERMODYNAMICS AND KINETICS ASPECTS OF THE GRAPHITE-LITHIUM NEGATIVE ELECTRODE FOR LITHIUM-ION BATTERIES -- CHARACTERIZATION OF ANODES BASED ON VARIOUS CARBONACEOUS MATERIALS FOR APPLICATION IN LITHIUM-ION CELLS -- A CARBON COMPOSITE FOR THE NEGATIVE ELECTRODE OF LI-ION BATTERIES -- ELECTROCHEMICAL INTERCALATION OF PF¯6 AND BF¯4 INTO SINGLE-WALLED CARBON NANOTUBES -- SURFACE TREATED NATURAL GRAPHITE AS ANODE MATERIAL FOR HIGH-POWER LI-ION BATTERY APPLICATIONS -- EMERGING METAL/CARBON COMPOSITE ANODES FOR NEXT GENERATION LITHIUM-ION BATTERIES -- ON THE THEORETICAL PREREQUISITES FOR APPLICATION OF NOVEL MATERIALS IN PROMISING ENERGY SYSTEMS -- CAPABILITIES OF THIN TIN FILMS AS NEGATIVE ELECTRODE ACTIVE MATERIALS FOR LITHIUM-ION BATTERIES -- COMPOSITE ANODE MATERIALS FOR HIGH ENERGY DENSITY LITHIUM-ION BATTERIES -- ELECTROCHEMICAL ACTIVITY OF CARBONS MODIFIED BY d-METAL COMPLEXES WITH ETHANOLAMINES -- METAL-GRAPHITE COMPOSITS AS MATERIALS FOR ELECTRODES OF LITHIUM-ION BATTERIES -- ELECTROCHEMICAL PERFORMANCE OF Ni/Cu-METALLIZED & CARBON-COATED GRAPHITES FOR LITHIUM BATTERIES -- NEW NANO- THROUGH MACRO-CARBONS FOR ENERGY SYSTEMS: SYNTHESIS, MODELING, CHARACTERIZATION -- STABILIZATION OF GRAPHITE NITRATE VIA CO-INTERCALATION OF ORGANIC COMPOUNDS -- ELECTROCHEMICAL STABILITY OF NATURAL, THERMALLY EXFOLEATED AND MODIFIED FORMS OF GRAPHITE TOWARDS ELECTROCHEMICAL OXIDATION -- LOW TEMPERATURE SYNTHESIS OF GRAPHITE FROM IRON CARBIDE -- HIGH RESOLUTION TRANSMISSION ELECTRON MICROSCOPY IMAGE ANALYSIS OF DISORDERED CARBONS USED FOR ELECTROCHEMICAL STORAGE OF ENERGY -- ELECTROLYSIS OF CARBAMIDE-CHLORIDE MELTS AT INERT ELECTRODES -- GRAPHITE INTERCALATION AS A WAY TO CARBON-CARBON COMPOSITES AND CARBON NANOSCROLLS -- CARBONS IN THE CATHODES OF LITHIUM-ION BATTERIES; ALTERNATIVE FORMS OF MnO2, CATHODE / CARBON MODELING -- DIAGNOSTIC EVALUATION OF POWER FADE PHENOMENA AND CALENDAR LIFE REDUCTION IN HIGH-POWER LITHIUM-ION BATTERIES -- MODELING OF ELECTROCHEMICAL PROCESSES IN THE ELECTRODES BASED ON SOLID ACTIVE REAGENTS AND CONDUCTIVE CARBON ADDITIVES -- ON THE OPTIMAL DESIGN OF AMORPHOUS MANGANESE OXIDE FOR APPLICATIONS IN POWER SOURCES -- INVESTIGATION OF CATHODIC MATERIALS BASED ON DIFFERENT TYPES OF MnO2/CARBON -- INVESTIGATION OF THIN-FILM ELECTRODE MATERIALS AS CATHODIC ACTIVES FOR POWER SOURCES -- SYNTHESIS OF MIXED OXIDES USING POLYBASIC CARBOXYLIC HYDROXY-AND AMINO-ACID ROUTES: PROBLEMS AND PROSPECTS -- IMPROVED ELETROCHEMICAL PROPERTIES OF SURFACE-COATED Li(Ni,Co,Mn)O2 CATHODE MATERIAL FOR Li SECONDARY BATTERIES.
Keywords: Lasers; Photonics; Energy storage; Materials science; Electrochemistry; Energy systems; Optical materials; Electronic materials; Optics, Lasers, Photonics, Optical Devices; Energy Storage; Materials Science, general; Electrochemistry; Energy Systems; Optical and Electronic Materials